Marine biogeographic realms and species endemicity. Issue 1 (December 2017) - Costello, Mark; Tsai, Peter; Wong, Pui; Cheung, Alan; Basher, Zeenatul; Chaudhary, Chhaya
Abstract Marine biogeographic realms have been inferred from small groups of species in particular environments (e.g., coastal, pelagic), without a global map of realms based on statistical analysis of species across all higher taxa. Here we analyze the distribution of 65, 000 species of marine animals and plants, and distinguish 30 distinct marine realms, a similar proportion per area as found for land. On average, 42% of species are unique to the realms. We reveal 18 continental-shelf and 12 offshore deep-sea realms, reflecting the wider ranges of species in the pelagic and deep-sea compared to coastal areas. The most widespread species are pelagic microscopic plankton and megafauna. Analysis of pelagic species recognizes five realms within which other realms are nested. These maps integrate the biogeography of coastal and deep-sea, pelagic and benthic environments, and show how land-barriers, salinity, depth, and environmental heterogeneity relate to the evolution of biota. The realms have applications for marine reserves, biodiversity assessments, and as an evolution relevant context for climate change studies. Global maps of biogeographic realms help to understand the geological and ecological processes that gave rise to species distributions, yet a marine realm map has been lacking. Here, Costello et al. use a database of over 65, 000 species to reveal 30 marine biogeographic realms and high rates of species endemicity.